Consumer satisfaction on the adoption of e-payment among millennials in Malaysia during Covid 19 pandemic - Md Yusoff, Muhammad Faiz; Jusoh, Nur Aniza Quantaniah; Abu Seman, Noor Aslinda (Penerbit UTHM, 2022)
The Pandemic Covid-19 had hugely impacted businesses and economy in every sector of the world through the implementation of Lockdowns and Movement Control Order (MCO). This situation has unavoidably caused a worldwide monetary decline (Cheng, 2020 & UNDP, 2020). , The MCO situation has limited the normal face to face retailing activity and affected consumer goods and the retail industry. Stores of essential items along with meals, groceries, and healthcare experienced extended call for opportunities for serving purchasers at home, at the same time as facing demanding situations of stock, supply chain control, shipping, and maintaining their facility a secure environment (Roggeveen & Sethuraman, 2020).